Patient and Physician Perceptions of the Impact of Electronic Health Records on the Patient–Physician Relationship - Eberts, Margaret; Capurro, Daniel (Applied Clinical Informatics, 2019)
Objectives Limited studies have been performed in South America to assess patient and physician perceptions of electronic health record (EHR) usage. We aim to study the perceptions of patients and physicians regarding the impact of EHRs on the patient–physician relationship.Methods We use a survey instrument to assess the physician computer experience and opinions regarding EHR impact on various aspects of patient care. An additional survey is used to assess patient opinions related to their medical visit. Surveys are administered in two outpatient clinics in a private, academic health care network.Results While a majority of physicians believed that EHRs have an overall positive impact on the quality of health care, many physicians had negative perceptions of the impact of EHRs on the patient–physician relationship. A majority of patients felt comfortable with their physician's use of the EHR and felt that their physician was able to maintain good personal contact while using the computer.Conclusion Although physicians believe EHRs have a generally positive impact on the overall quality of care, the EHR's impact on the patient–physician relationship is still of concern. Patients do not perceive a negative interference from the EHR on the patient–physician relationship.
Keywords: electronic health records and systems; patient records; specific types